Depresión severa en un adolescente de 17 años - Cordova Ramos, Angelo Marcelo (2021)
The present case study has been developed with the purpose of evaluating the severity of depression present in a 17-year-old adolescent from the city of Babahoyo and in turn to elaborate a proposal for a psychotherapeutic intervention that maintains everything related to the depression and its causes and consequences. From the approach of cognitive behavioral therapy, the therapy chosen to carry out the psychotherapeutic intervention and in turn carry out this case study due to the patient's demand, four techniques were used that were very helpful for the patient to understand the problems that they were causing her negative thoughts both physically and mentally and improving the quality of life of the patient.